Influence of Rice Husk Ash on the Properties of Concrete - KAD, NISHANT; VINOD, M. (IJRDO -Journal of Computer Science Engineering, 2015)
This paper summaries ongoing researches about the effect on the properties of concrete(compressive strength, flexural strength initial and final setting time, workability and durability)on the partial replacement of rice husk ash with cement by 0%,10%,20% and 30% of weight tomake the concrete environment friendly and less costly. The optimum replacement (withimproved properties of concrete) is concluded.